Kolaborasi antara Pemerintah Desa, Stakeholder dan Masyarakat dalam Pengelolaan Wisata Alam Citumang Desa Bojong Kecamatan Parigi Kabupaten Pangandaran - Dicka Rusmawan Budia Kusumah; Kiki Endah; Agus Nurulsyam Suparman (International Forum of Researchers and Lecturers, 2025)
This research is motivated by the importance of implementing sustainable tourism management principles in the management of Citumang Nature Tourism, Bojong Village, Parigi District, Pangandaran Regency. This management not only emphasizes the utilization of economic value, but must also pay attention to the preservation of the natural environment, socio-cultural values and aspects, and the active involvement of the local community. This aims to ensure that the benefits of Citumang's existence can be felt by all levels of society. The purpose of this study is to determine the form and effectiveness of collaboration between the village government, stakeholders, and the community in managing this nature tourism. This study uses a qualitative method with data collection techniques through literature studies and field studies. Data analysis is carried out in three stages, namely data collection, data reduction, and data presentation. The results of the study indicate that the collaboration between the village government, stakeholders, and the community still faces several obstacles. Problems identified include the lack of official licenses or professional guide certificates for tour guides, an unclear organizational structure resulting in weak coordination between the village government and tour guide groups, limited proactive leadership, which reduces community motivation and participation in tourism development, low community involvement in the planning and implementation of tourism activities, and a lack of effective promotion to attract visitors. These conditions have resulted in the suboptimal development of Citumang's tourism potential as a leading regional destination. This study recommends the establishment of a clear organizational structure, increased human resource capacity through guide training and certification, strengthening the role of visionary and inclusive leadership, increasing community participation in all stages of tourism management, and implementing creative and targeted promotional strategies. This will enable Citumang's nature tourism management to be more effective, sustainable, and provide optimal benefits for all stakeholders.